2019
DOI: 10.1002/mdc3.12850
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Activity Monitor Data from Devices Worn on the Wrist and the Waist in People with Parkinson's Disease

Abstract: Background It is unclear if it is appropriate for people with Parkinson's disease (PD) to wear activity monitors on the wrist because of the potential influence of impairments on the data. Objective The objective of this study was to determine (1) whether activity monitor data collected from devices worn at the wrist and waist are comparable and (2) the contribution of PD impairments to any differences in step and activity counts at the wrist and waist. Methods A total of 46 community‐dwelling people with PD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Despite the proven benefits of PA on motor and non-motor symptoms, people with PD are generally less physically active than people of similar age without the disease. Community-dwellers who are independently ambulatory take approximately 5000 steps/day [ 16 18 ], even those who are newly diagnosed [ 19 ] and prior to the commencement of anti-Parkinson medications [ 20 ]. When viewed in relation to the approximated 7000 steps/day required of older adults in order to meet health recommendations [ 21 ], the activity patterns of people with PD reflect sedentary lifestyles [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the proven benefits of PA on motor and non-motor symptoms, people with PD are generally less physically active than people of similar age without the disease. Community-dwellers who are independently ambulatory take approximately 5000 steps/day [ 16 18 ], even those who are newly diagnosed [ 19 ] and prior to the commencement of anti-Parkinson medications [ 20 ]. When viewed in relation to the approximated 7000 steps/day required of older adults in order to meet health recommendations [ 21 ], the activity patterns of people with PD reflect sedentary lifestyles [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge for people with PD is the achievement of sustained bouts of MVPA [ 17 19 ], a pattern even apparent among those with higher step counts [ 23 ]. On average, people with PD appear to spend 75% of their waking time in SB, and between 2 and 6% of their total time in MVPA [ 16 , 17 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, an optimal and standardized method remains for establishing [15]. The number and location of the sensors are key aspects for the success of assessments with TOMs, especially in a free-living context [8,16]. To increase wearing compliance without hindering the precision of data collection the number of sensors should be kept to a minimum, and the least obtrusive devices preferred [8,16].…”
Section: ) Where To Place the Sensor?mentioning
confidence: 99%
“…The number and location of the sensors are key aspects for the success of assessments with TOMs, especially in a free-living context [8,16]. To increase wearing compliance without hindering the precision of data collection the number of sensors should be kept to a minimum, and the least obtrusive devices preferred [8,16]. Today, although the lower back is not considered the most comfortable and unobtrusive location, it has been shown that a single sensor (accelerometer) in this location is able to capture with precision, physical activity and gait parameters in a laboratory and freeliving context [16,17].…”
Section: ) Where To Place the Sensor?mentioning
confidence: 99%
See 1 more Smart Citation